KAJIAN AKAD PEMBIAYAAN LOGAM MULIA UNTUK MASYARAKAT PADA PEGADAIAN SYARIAH - Irayana Harpen (MENARA RIAU, 2014)
Pawn Shari'ah or rahn at first is one of the products offered by Islamic Bank . Bank Muamalat Indonesia (BMI) as the first Islamic bank in Indonesia has entered into a collaboration with Pawnshop , and gave birth to Sharia Pledge Service Unit (now, Pawnshop Branch Sharia ) which is an independent institution based on Islamic principles . One of the products on offer is the sharia mortgage financing MULIA ( Murabaha Precious Metals Investing For Eternal ) . From the observation of the writer , Implementation murabaha contract and financing agreement MULIA Rahn in accordance rukunnya terms and according to Islamic law , both involving al - ' Akid ( the parties ) , al - ma'kud ' alaih (object agreement ) or sighat ( consent and granted ) . MULIA with murabaha financing and rahn contract does not include the two covenants in a prohibited transaction , because the murabaha contract as the contract agreement was essentially rahn ( pledge ) is asessoir . Barriers to implementation of the agreement MULIA murabaha financing and rahn on Pawn Sharia are the following factors : first , the presence of factor legal opinion that most people murabaha financing agreement and MULIA with rahn contract is included in the category of " Shofqotaini shofqoh wahidah fi " ( a transaction with two contract ) which is prohibited by the Prophet , since the collateral ( al - marhun ) has not been handed over and not owned by the customer , although opinions are more popular and more powerful allowing MULIA financing because it contains no riba and gharar and collateral belonged to customers when the murabaha contract . Second , the implementing agreement factor mainly from the pawnshop employee where customers ( rahin ) often do not fully understand the contract that has been agreed upon by as blank contract has been provided by the mortgage and the terms of the agreement are written in blank contract . Similarly, from the pawn shops do not proactively provide clear information to clients on contract that is being made so that the contract is not legally flawed because there is a hidden factor that sense light or not . Third , factor means that the Shari'ah has not backed mortgage depository eligible security . Because pawn goods are precious possessions , it requires secure storage . After all the murabaha contract - rahn , Pawn sharia does not charge rent ( ijara ) , hence the collateral security ( marhun ) is also a consideration in the closing contract customer murabaha sharia - rahn with pawn shops . Fourth , factors of society where sharia mortgage financing to precious less socialized . Pawnshops in the public eye is getting financing ( debt ) in the form of money against immovable property . Medium financing is financing to precious have the gold then the gold as collateral . Though that may be a pawn goods ( al - marhun ) is any item of property that can be sold traded , can include: jewelry , electronics , vehicles , and other items that are considered valuable and needed . Fifth , cultural factors are less disciplined and punctual consumerist culture . If customers are late paying installments for a day , then exposed keterlamabatan fines and penalties to settle the installment keterlamabatan can accumulate so very burdensome for customers . Such fines is not unlike like the interest charged by conventional mortgage , although the proceeds of the settlement payment the customer will be reserved entirely for social purposes